PENERAPAN PEMBERIAN PENGUATAN (REINFORCEMNT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA TENTANG DAUR HIDUP MAKHLUK HIDUP KELAS IV SD GMIT KOLHUA KOTA KUPANG - Siki, Kevin Roger; Koroh, Taty R.; Benu, Adam Bol Nifu (Journal of Character and ELementary Education, 2024)
The aim of this research is to improve student learning outcomes regarding the life cycle of living things in class IV SD GMIT Kolhua, Kupang City by using the application of reinforcement methods. Based on the results of initial observations by researchers at GMIT Kolhua Elementary School, Kupang City, totaling 23 students, it was found that in reality, the student learning outcomes showed that 80% had not reached a score above the KKM, namely 70. This is because teachers do not provide reinforcement so students are less motivated in the learning process because students feel that there is no appreciation for their participation in learning so student learning outcomes still look low. The type of research used in this research is Classroom Action Research (PTK) which includes four stages of planning, implementation, observation/test, and reflection. Data collection techniques were carried out using observation sheets and tests. The research results in cycle I received poor criteria with a complete presentation of student learning outcomes obtained at 56.52%, while student learning outcomes in cycle II received very good criteria (SB). With the completeness of the presentation, the students obtained 86.96. So the learning method is student learning outcomes, while the data from student observations in cycle I, students obtained a total score of 1,1561.11 with an average of 67.87 and received adequate criteria (C), while in cycle II the student activity score increased to 2,038, 89 with an average score of 88.65 and received very good criteria (SB). Based on the results of student observations above, there was an increase from cycle I to cycle II of 13.04%.